Analisis Faktor Penentu Tingkat Kepuasan Pemberi Kerja Alumni Universitas Jambi - Noferdiman Noferdiman; Firmansyah Firmansyah; Fachroerrozi Hoesni; Yusma Damayanti; Indra Sulaksana (Universitas Batanghari Jambi, 2022)
This study aims to analyze the satisfaction level of Jambi University alumni employers and aspects of higher education services that must be optimized to increase Jambi University alumni job satisfaction. The research method used is a survey method with a sampling technique that is Stratified Random Sampling, each strata is selected one sampling unit with a simple random sampling technique. Measurement of qualitative variables using a questionnaire in the form of questions with Summated Rating's Scala Likert which was tested for validity and reliability. Aspects of satisfaction analysis include: Integrity (ethics and morals), Expertise in the field of science (main competence), Broadness of insight between disciplines, Leadership, Teamwork, Foreign language skills, Communication skills, Use of information technology, and self-development. To analyze the determinants of the level of satisfaction of the Jambi University alumni employer used Path Analysis. The overall satisfaction index of Jambi University alumni is still lacking with a score of 73.78 or C. Then, the satisfaction index of Jambi University alumni who work in Government agencies (Provincial and Regency/City Governments) is still lacking with a value of 73.50 or C. Furthermore the satisfaction index of Jambi University alumni who work in companies (Private, BUMN, Foundation) is still lacking with a score of 74.76 or C. The ability of Jambi University alumni who work in government agencies and companies to solve problems is the biggest or most decisive factor on employer satisfaction Jambi University alumni.